Poradnictwo biograficzne. O pomocy psychopedagogicznej w biegu życia człowieka - Piorunek, Magdalena (Wydawnictwo Naukowe UAM, 2009)
This work is addressed to people in their course of life with a special emphasis on the functioning of the educational and professional sphere. Very dynamic socio-cultural transformations connected with changes in the consciousness, cultural pluralism and axiological relativism, dominating changeability, uncertainty and unpredictability of human life, as well as economical changes (‘a professional earthquake’) constitute a basis for the development of the counselling. It is addressed to people on different biographical stages, focusing prophylactic and pro especially on the crucial events in life, periods of transition, or a time when people commence some routine actions in-between the turning points in their lives. It has therapeutic, motional functions. Its role in the human biography is analysed from an individual (as it appeals to the biographical narration case) and social perspective. The main task of counselling nowadays is assisting human beings in their course of life, in the path of their development, characterized, fi rst and foremost, in the context of a permanent social change.
Biographical counselling. On the psycho-pedagogical aid in the course of humans life’ presents the problems of the contemporary counselling